A Survey on LoRa for Smart Agriculture: Current Trends and Future Perspectives - Pagano, Antonino; Croce, Daniele; Tinnirello, Ilenia; Vitale, Gianpaolo (IEEE internet of things journal, 2023)
This paper provides a survey on the adoption of LoRa in the agricultural field, and reviews state-of-the-art solutions for Smart Agriculture, analyzing the potential of this technology in different infield applications. In particular, we consider four reference scenarios, namely irrigation systems, plantation and crop monitoring, tree monitoring, and livestock monitoring, which exhibit heterogeneous requirements in terms of network bandwidth, density, sensors' complexity, and energy demand, as well as latency in the decision process. We discuss how LoRa-based solutions can work in these scenarios, analyzing their scalability, interoperability, network architecture, and energy-efficiency. Finally, we present possible future research directions and point out some open issues which might become the main research trends for the next years.